Review of Al2O3-based composite separators for lithium-ion battery - Abavi Torghabeh , Naghmeh; Bazli, Leila (Journal of Composites and Compounds, 2025)
Lithium-ion batteries (LIBs) have faced safety and performance challenges due to aluminum oxide (Al2O3)-based composite separators. This review aims to give you a comprehensive summary of recent advances in the design, fabrication, and application of Al2O3-modified separators. With their high surface activity, excellent hydrophilicity, and excellent thermal stability, Al2O3 ceramics are widely used as separators to improve thermal resistance, electrolyte wettability, and ionic conductivity, while effectively preventing lithium dendrite growth and improving mechanical strength, among other properties. A variety of composite architectures are discussed, including polymer/Al2O3 blends, ceramic-coated polyolefin membranes, and nanocellulose/Al2O3 hybrids, which have superior electrochemical properties, high porosity, and robust antishrinkage properties. Various mechanisms explain how Al2O3 contributes to improved separator performance, and the advantages of Al2O3-based systems in terms of safety, cycle stability, and rate performance are clearly demonstrated. Furthermore, the review outlines current challenges and provides perspectives on future research directions towards the practical implementation of Al2O3-based composite separators in high-performance LIBs of the future.